Об одном результате типа теоремы Г. Сегё - С. А. Вагаршакян (Հայաստանի ԳԱԱ)
В этой статье приводится новый результат типа хорошо известной теоремы Г. Сегё и А. Колмогорова о наилучшем приближении аналитическими полиномами в весовых пространствах Lp. Результаты такого типа играют существенную роль в теории предсказания стационарных процессов. Хорошо известно, что точность наилучшего предсказания на один шаг вперёд, не зависит от р. В данной статье мы докажем, что в случае предсказания на два шага вперёд получаются разные результаты для р = 2 и р = ∞. The paper proves a new result similar to the well known theorems of G. Szego and A. Kolmogorov on the best approximation by analytic polynomials in weighted Lp spaces. Such results are essential in prediction theory for stationary processes. It is well known, that for one step prediction, the size of the best approximation is the same for all p. The paper proves that for two step prediction the best approximation sizes are different for p = 2 and p = ∞. The paper proves a new result similar to the well known theorems of G. Szego and A. Kolmogorov on the best approximation by analytic polynomials in weighted Lp spaces. Such results are essential in prediction theory for stationary processes. It is well known, that for one step prediction, the size of the best approximation is the same for all p. The paper proves that for two step prediction the best approximation sizes are different for p = 2 and p = ∞.
Keywords: Science; Mathematics